Polymeric nanofibrous substrates stimulate pluripotent stem cells to form three‐dimensional multilayered patty‐like spheroids in feeder‐free culture and maintain their pluripotency. (25th November 2014) - Alamein, Mohammad A.; Wolvetang, Ernst J.; Ovchinnikov, Dmitry A.; Stephens, Sebastien; Sanders, Katherine; Warnke, Patrick H.
Abstract: Expansion of pluripotent stem cells in defined media devoid of animal‐derived feeder cells to generate multilayered three‐dimensional (3D) bulk preparations or spheroids, rather than two‐dimensional (2D) monolayers, is advantageous for many regenerative, biological or disease‐modelling studies. Here we show that electrospun polymer matrices comprised of nanofibres that mimic the architecture of the natural fibrous extracellular matrix allow for feeder‐free expansion of pluripotent human induced pluripotent stem cells (IPSCs) and human embryonic stem cells (HESCs) into multilayered 3D 'patty‐like' spheroid structures in defined xeno‐free culture medium. The observation that IPSCs and HESCs readily revert to 2D growth in the absence of the synthetic nanofibre membranes suggests that this 3D expansion behaviour is mediated by the physical microenvironment and artificial niche provided by the nanofibres only. Importantly, we could show that such 3D growth as patties maintained the pluripotency of cells as long as they were kept on nanofibres. The generation of complex multilayered 3D structures consisting of only pluripotent cells on biodegradable nanofibre matrices of the desired shape and size will enable both industrial‐scale expansion and intricate organ–tissue engineering applications with human pluripotent stem cells, where simultaneous coupling of differentiation pathways of all germ layers from one stem cell source may be required for organ formation. Copyright © 2014 John Wiley & Sons, Ltd.